RETRACTED ARTICLE: The relationship between hemodialysis mortality and the Chinese medical insurance type. (1st January 2019) - Yao, Xi; Chen, Shaohua; Lei, Wenhua; Shi, Nan; Lin, Weiqiang; Du, Xiaoying; Zhang, Ping; Chen, Jianghua
Statement of Retraction: We, the Editor and Publishers of Renal Failure, have retracted the following article: Xi Yao, Shaohua Chen, Wenhua Lei, Nan Shi, Weiqiang Lin, Xiaoying Du, Ping Zhang & Jianghua Chen, The relationship between hemodialysis mortality and the Chinese medical insurance type, Renal Failure, 41:1, 2019, 742–749, https://doi.org/10.1080/0886022X.2019.1652648 . The above article has been retracted due to Publisher error as it is an earlier version of an article that was ultimately accepted and published in Renal Failure . The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".